The biobank of barretos cancer hospital: 14 years of experience in cancer research - Neuber, Ana Caroline; Tostes, Cássio Hoft; Ribeiro, Adeylson Guimarães; Marczynski, Gabriella Taques; Komoto, Tatiana Takahasi; Rogeri, Caroline Domingues; da Silva, Vinicius Duval; Mauad, Edmundo Carvalho; Reis, Rui Manuel; Marques, Márcia M. C. (Cell and tissue banking, 2022)
Despite the developments in cancer research over years, cancer is still one of the leading causes of death worldwide. In Brazil, the number of cancer cases for the several next years (2020–2022) is expected to increase up to 625,000. Thus, translational research has been vital to determine the potential risk, prognostic, and predictive biomarkers in cancer. Therefore, Barretos Cancer Hospital implemented a biobank (BB-BCH) in 2006, which is responsible for processing, storage, and provision of biological materials from cancer and non-cancer participants. Hence, this article aimed to describe BB-BCH’s history, experiences, and outcomes and explore its impact on Brazilian translational oncology research scenario. BB-BCH has a multidisciplinary team who are responsible for guaranteeing the quality of all processes as recommended by international guidelines for biobanks. Furthermore, BB-BCH has ample equipment to ensure the quality of all material requested by researchers as genetic material (DNA and RNA) and/or entire biospecimens. From 2006 to 2019, BB-BCH contained 252,069 samples from 44,933 participants, the whole collection is represented by 15 different types of biospecimens collected from them. According to our data, the most collected and stored topography in men is head and neck (29%); in women is breast (28%); and in children is torso and limb (27%) samples. Finally, we supported national and international consortia and projects such as The Cancer Genome Atlas. BB-BCH is a vital knowledge source for scientific community, enabling the development of high-quality studies, with a wide variety of tumor categories and high national representativeness of Brazilian population.